2004
DOI: 10.1097/01.ju.0000135337.71154.60
|View full text |Cite
|
Sign up to set email alerts
|

Dimercapto-Succinic Acid Scintigraphy Instead of Voiding Cystourethrography for Infants With Urinary Tract Infection

Abstract: DMSA scintigraphy in infants with UTI may replace VCU as a first line investigation. A strategy to perform VCU in only patients with renal lesions is proposed. In this study 147 of 303 VCUs would have been unnecessary as only 1 child with a damaged kidney was missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
2
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(130 citation statements)
references
References 19 publications
11
105
2
11
Order By: Relevance
“…But to avoid a missed diagnosis, parents should be aware of the possibility of a recurring UTI and be advised to seek prompt treatment of any suspected reinfection. 14 This viewpoint is consistent with that of other recent studies, 4,6,17,20,29 all of which used the same top-down approach as well. It is worth emphasizing that the high sensitivity of the DMSA scan for the detection of dilating VUR in this study was because the scan was performed acutely within 1 week of the diagnosis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…But to avoid a missed diagnosis, parents should be aware of the possibility of a recurring UTI and be advised to seek prompt treatment of any suspected reinfection. 14 This viewpoint is consistent with that of other recent studies, 4,6,17,20,29 all of which used the same top-down approach as well. It is worth emphasizing that the high sensitivity of the DMSA scan for the detection of dilating VUR in this study was because the scan was performed acutely within 1 week of the diagnosis.…”
Section: Discussionsupporting
confidence: 81%
“…15,16 The rate of VUR in patients with abnormal DMSA was 41.3% (164/ 397), which was also in agreement with previous data. 17 However, we noticed a relatively high percentage of dilating VUR (28.9% of patients; 187/1046 = 17.8% of renal units), which was higher than that reported in some studies, 5,18 but was close to the proportion found in other reports. 4,19,20 The large number of cases of dilating VUR in our country may be due to several reasons.…”
Section: Discussioncontrasting
confidence: 53%
“…[22][23][24][25] Renal scintigraphy can detect the majority of the patients with moderate to severe reflux (grade 3 or higher). [21,26] Our findings also indicated the presence of a relationship between high-grade VUR and renal scarring. In our study, renal scarring was found relatively more frequently in patients aged 25-60 months with high VUR frequency.…”
Section: Discussionsupporting
confidence: 59%
“…41,44,51,56,57,62,63 The distributions of different reflux grades among children who had VUR are shown in Fig 4. There is significant variability in the relative predominance of each reflux grade, but grades II and III consistently are the most common. With the exception of the study by Camacho et al, 41 all studies showed grades IV and V to be the least frequent, and grade V accounted for 0% to 5% (weighted average: 3%) of reflux.…”
Section: Prevalence Of Vurmentioning
confidence: 99%